Harnessing the electronic health care record to optimize patient safety in primary care: framework for evaluating e–safety-netting tools - Black, GB; Bhuiya, A; Friedemann Smith, C; Hirst, Y; Nicholson, BD (JMIR Publications Inc., 2022)
The management of diagnostic uncertainty is part of every primary care physician's role. e-Safety-netting tools help health care professionals to manage diagnostic uncertainty. Using software in addition to verbal or paper based safety-netting methods could make diagnostic delays and errors less likely. There are an increasing number of software products that have been identified as e-safety-netting tools, particularly since the start of the COVID-19 pandemic. e-Safety-netting tools can have a variety of functions, such as sending clinician alerts, facilitating administrative tasking, providing decision support, and sending reminder text messages to patients. However, these tools have not been evaluated by using robust research designs for patient safety interventions. We present an emergent framework of criteria for effective e-safety-netting tools that can be used to support the development of software. The framework is based on validated frameworks for electronic health record development and patient safety. There are currently no tools available that meet all of the criteria in the framework. We hope that the framework will stimulate clinical and public conversations about e-safety-netting tools. In the future, a validated framework would drive audits and improvements. We outline key areas for future research both in primary care and within integrated care systems.